Designing Hollow Structured Materials for Sustainable Electrochemical Energy Conversion - Singh B.; Indra A. (My University, 2025)
Hollow-structured materials with well-defined boundaries and interior cavities have attained special attention in the field of energy conversion because of their promising electrochemical performance. The hollow-structured materials offer unique characteristics like a high surface-to-volume ratio, low density, and short mass and charge transport lengths compared to the hierarchical structure. In fact, tremendous efforts have been undertaken to design new hollow-structured materials with diverse structural and morphological features. In this respect, synthetic strategy plays a crucial role, and approaches like template-directed synthesis, selective etching, Kirkendall effect, Ostwald ripening, ion exchange, and so on have been explored to achieve the special structural features. A wide range of materials like metal oxides, sulfides, phosphides, and others have been demonstrated with excellent electrocatalytic activity. In general, complex multi-shelled hollow spheres, cubes, dodecahedrons, and others have been found to produce better electrochemical performance compared to the corresponding single- or double-shelled structure. In addition, bubble‐in‐bubble-, tube‐in‐tube-, and wire‐in‐tube-type hollow structures are demonstrated to achieve the desired activity. As this volume deals with materials for designing energy applications, special attention is paid in this chapter to find out the importance of the hollow structure, designing these materials, and applying them to electrochemical energy conversion. The progress and prospects of this newly growing field are discussed in the light of practical applications. © 2024 selection and editorial matter, Piyush Kumar Sonkar and Vellaichamy Ganesan; individual chapters, the contributors.